STRATEGI PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF DALAM MENINGKATKAN BERPIKIR KRITIS SISWA - Ulah Al Chumairoh Machfud, Nailul; Nur Isnaini , Ade; Bariyyah , Khoirul (ILJ: Islamic Learning Journal, 2024)
This study aims to analyse the strategy of using interactive multimedia-based learning media in improving students' critical thinking in Fiqh learning subjects at Madrasah Aliyah Unggulan Nur Al-Jadid Waru Sidoarjo. This research uses a qualitative approach, data collection methods using interviews, observation and documentation, descriptive analysis. The results showed that the use of interactive multimedia is able to create a more interesting and interactive learning environment, thus motivating students to be more active in the learning process. This interactive multimedia provides a variety of visual and audio resources that support the understanding of complex Fiqh concepts. Through this method, students can more easily understand and analyse the material, as well as engage in discussion and critical problem solving. The research data showed a significant improvement in students' critical thinking skills after the implementation of this strategy, which was evident in their ability to identify problems, analyse arguments and devise solutions based on Fiqh principles. Thus, the use of interactive multimedia-based learning media is proven effective in improving the quality of learning and students' critical thinking skills in Fiqh subjects.